Measurement of factors for credit recovery failures - CHOI, Yeonsoo (KDI School, 2021)
The debt adjustment system is a policy tool that has been realized in many countries. The credit recovery system not only helps debtors recover their credit but also relieves job insecurity caused by foreclosures and collections. However, not everyone benefits from the credit recovery system. Some debt-adjustment applicants experience a mid- term failure. To date, there were many studies that relied on surveys of people who applied for credit recovery, such as individual rehabilitation and bankruptcy. However, debtors who have experienced failure are reluctant to take the survey, making it difficult to do accurate analysis. This study analyzes the causes of credit recovery failures and suggests complementary points that can help regain credit. In particular, people with unstable incomes, such as temporary or unemployed workers, are less likely to succeed in recovering their credit. In addition, many of the dropouts were made early in the repayment period. On this basis, this study suggests that job consulting and credit consulting are helpful. These results can also be used to present complementary policies.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: Debt; Finance, Personal